The changing constitution - Harrison, Kevin (Edinburgh University Press, 2006)
Providing an introduction to the topical subject of constitutional change in Britain, this book considers the historical origins of the constitution but focuses on reforms and their likely impact. It includes chapters on: The Legislature: The House of Commons and the House of Lords; The Executive; Electoral Reform and Referenda; and more.
Keywords: Constitutional history -- Great Britain.; Great Britain -- Politics and government -- 20th century.; Great Britain -- Politics and government -- 21st century.; Grande-Bretagne -- Politique et gouvernement -- 20e siècle.; Grande-Bretagne -- Politique et gouvernement -- 21e siècle.; LAW -- Constitutional.; LAW -- Public.; POLITICAL SCIENCE -- Constitutions.; Constitutional history; Politics and government; Great Britain; 1900 - 2099